African Philosophy and the Roots of Leadership And Ethics in Swahili Proverbs (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This article explores African philosophy and the foundations of leadership and ethics, drawing on Swahili proverbs. Primary data were collected from library sources. Library-based reading methods were employed to collect primary data. Reviews of documents used to validate the primary data were obtained from electronic and library sources. Sociological Theory was utilized in analyzing the data. The main premise of this theory is that literary and artistic works cannot be understood without considering the historical, political and social contexts in which they were produced. The data analyses were consistent with the principles of the selected theory. A descriptive approach was used to present the data. The findings indicate that reflecting African philosophy in Swahili literature emphasizes solidarity, human dignity, accountability, justice and integrity as essential foundations of good leadership and ethics. Furthermore, literature, through examples of leaders and society, underscores the importance of unity, justice and accountability. Consequently, literature is a vital tool for promoting ethical leadership and effective leadership while also supporting social welfare, peace and sustainable development. This confirms that Swahili literature reflects African values that foster social well-being. This article recommends that, to strengthen leadership and ethics, schools and communities should promote education emphasizing African philosophy, including concepts such as Ubuntu [I am because we are], solidarity, accountability, justice and respect for every human being.